2020
DOI: 10.3390/ijerph17186881
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sexual Habits and Sexually Transmitted Infections at a Specialised Centre in Granada (Spain)

Abstract: Sexually transmitted infections are an important public health issue. The purpose of this study is to analyse the association between different sexual habits and the prevalence of sexually transmitted infections in the population of Granada who consult with a specialised centre. An observational, cross-sectional study was conducted based on the medical records of 678 people from the Sexually Transmitted Diseases and Sexual Orientation Centre of Granada, who were diagnosed positively or negatively with a sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This observation differs from that of a prospective study conducted in Paris, in which the primary mode of sexual exposure was anal sex in 65% of patients, while vaginal intercourse accounted for only 26% of cases [ 12 ]. However, an observational, cross-sectional study of 678 patients in Spain found vaginal intercourse (99.2%) to be the commonest sexual method of HIV exposure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation differs from that of a prospective study conducted in Paris, in which the primary mode of sexual exposure was anal sex in 65% of patients, while vaginal intercourse accounted for only 26% of cases [ 12 ]. However, an observational, cross-sectional study of 678 patients in Spain found vaginal intercourse (99.2%) to be the commonest sexual method of HIV exposure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that people who performed oral activities have higher risks associated with STD/HIV transmission than those not. 56 Other serious risks that arise due to oral sex behavior include human papillomavirus infection, which causes oral squamous papilloma, oral verruca vulgaris, condyloma acuminata, focal epithelial hyperplasia, epidermoid carcinoma, and oropharyngeal squamous cell carcinoma. [57][58][59] One study from Indonesia proves a strong correlation between the activity of oral and anal among homosexuals and HPV infection (OR 6.854).…”
Section: Perspectives and Motives In Oral Sexmentioning
confidence: 99%
“…Condom use decisions also depend on sexual activity characteristics. For example, condom use is less prevalent in oral sex when compared to intercourse (Glynn et al, 2017;Habel et al, 2018;Leichliter et al, 2007;Molina & Tejada, 2018;Santa-Bárbara et al, 2020). Reasons to have condomless oral sex include wanting to have more pleasure, not having thought about it, not wanting to use condoms, or not having the risk of unplanned pregnancies, whereas reasons to use condoms when having oral sex include wanting to avoid diseases and to be more hygienic (Stone et al, 2006;Strome et al, 2022).…”
Section: Reasons For (Not) Using Condomsmentioning
confidence: 99%